1996
DOI: 10.1093/ajcn/64.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Neither raw nor retrograded resistant starch lowers fasting serum cholesterol concentrations in healthy normolipidemic subjects

Abstract: The question addressed was whether dietary resistant starch would lower serum cholesterol and triacylglycerol concentrations in healthy normolipidemic subjects. In a randomized single-blind 3 x 3 Latin-square study with corrections for any carryover effects, 27 males and 30 females consumed supplements containing glucose or resistant starch (RS) from raw high-amylose cornstarch (RS2) or from retrograded high-amylose cornstarch (RS3). The RS2 and RS3 supplements provided 30 g RS/d. Each type of supplement was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
2
29
1
1
Order By: Relevance
“…Many in vivo studies have shown that RS may be readily fermented by colonic microflora, but differences in fermentability were found (29). It has been claimed that starch is com pletely fermented by gut bacteria (12). Further study is needed to clarify the exact colonic process followed by the ingestion of different types of RS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many in vivo studies have shown that RS may be readily fermented by colonic microflora, but differences in fermentability were found (29). It has been claimed that starch is com pletely fermented by gut bacteria (12). Further study is needed to clarify the exact colonic process followed by the ingestion of different types of RS.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in nature of RS, study subjects as well as feeding regiments may be the contributing factors. In fact, the differences in RS have been suggested to play a role in glycemic response (12), wolf et al (22) have found no significant glucose lower ing action with RS from corn, whereas wakabayashi et al (21) have noticed a beneficial glycemic response with RS from potato.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study by Olesen et al (1995) there was no significant effect on blood cholesterol concentration by 50 g/d of raw potato starch or high amylose corn starch, but it was stressed that the baseline values fluctuated considerably, masking any minor effects. A more comprehensive study recently performed by Heijnen et al (1996) in healthy volunteers indicated that there was no significant effect of supplementing 30 g/d RS 2 or RS 3 to the diet on fasting levels of serum total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol, or triacylglycerols. Ranganathan et al (1994) observed, within an acute study, that a high amylose corn starch had no effect on blood non-esterified fatty acids (NEFA) and NEFA oxidation comparable with cellulose.…”
Section: E F F E C T S O N P L a S M A L I P I D Smentioning
confidence: 95%
“…Four randomised controlled trials were identified that presented evidence on resistant starch supplementation in relation to measures of energy intake, three of which were included in a meta-analysis (De Roos et al, 1995;Heijnen et al, 1996;Jenkins et al, 1998). One trial was not included in the meta-analysis as it was unclear which type of resistant starch subjects were supplemented with (Ells et al, 2005) (Cardio-metabolic review, energy intake and eating motivation chapter, p126-129).…”
Section: Resistant Starchmentioning
confidence: 99%